Influence of general anesthesia on outcomes after anterior circulation mechanical thrombectomy: results from the prospective international ASSIST registry - Hoffman, Haydn; Miralbés, Salvador; Naravetla, Bharath; Spiotta, Alejandro; Loehr, Christian; Martínez-Galdámez, Mario; McTaggart, Ryan; Defreyne, Luc; Vega, Pedro; Zaidat, Osama O.; Price, Lori Lyn; Liebeskind, David S.; et al. (Interventional neuroradiology, 2025)
Background - Multiple studies have evaluated whether general anesthesia (GA) improves outcomes after mechanical thrombectomy (MT) with mixed results. Many of these did not include procedural outcomes such as time to recanalization, degree of recanalization, and first pass effect (FPE). - Methods - The ASSIST registry, a prospective, global, multicenter registry of patients undergoing anterior circulation MT was used. Adults with internal carotid artery or M1/2 occlusions were included. The variable of interest was type of anesthesia used during MT, which was dichotomized to GA or non-GA. The outcomes of interest were time from arterial puncture to recanalization in patients who achieved extended thrombolysis in cerebral infarction (eTICI) ≥ 2b50 recanalization, final recanalization with eTICI ≥ 2c, first pass recanalization with eTICI ≥2 c (FPE), intraprocedural complications, 90-day favorable outcome (modified Rankin scale 0-2), symptomatic intracranial hemorrhage (sICH), any ICH, and early neurological deterioration (defined as an increase in NIHSS ≥ 4 points from baseline up to 48 hours after MT). Multivariable regression models were generated for each outcome. - Results - There were 1477 patients who underwent MT (38.9% under GA). In the multivariable analysis GA was not significantly associated with time from arterial puncture to recanalization (p = 0.08) but was significantly associated with greater odds of final recanalization with eTICI ≥ 2c (odds ration (OR) 1.62, 95% confidence interval (CI) 1.11-2.36). There was no difference in the odds of intraprocedural complications for the GA group (OR 0.73, 95% CI 0.28-1.92). GA was also not associated with 90-day favorable outcome, sICH, any ICH, END, or FPE. - Conclusion - GA for MT is associated with greater odds of eTICI ≥ 2c final recanalization.
Vorab online veröffentlicht: 2. Juni 2025
Gesehen am 24.09.2025